Temperature-dependent bandgap of (In,Ga)As via P5Grand: A Python Package for Property Prediction of Pseudobinary systems using Grand canonical ensemble - Han Gyu Seung; Yeu In Won; Ye, Kun Hee; Yoon SeungJae; Jeong, Tae Young; Lee, Seung Cheol; Hwang, Cheol Seong; Choi, Jung-Hae (Elsevier BV, 2022)
We introduce introduces an open-source program for calculating the properties of solid solutions, "Python Package for Property Prediction of Pseudobinary systems using Grand canonical ensemble" (P5Grand). P5Grand uses two main strategies to improve calculation efficiency: random configuration sampling and separate calculations of the strain energy induced by local compositional fluctuations within the grand canonical ensemble. P5Grand can efficiently calculate thermodynamic properties and any properties of interest for arbitrary solid solution as a function of temperature and composition using two input files. The efficiency of P5Grand is demonstrated by the bandgap prediction of (In,Ga)As.